Pemberdayaan Perempuan Kelompok UKM di Desa Jetis Kecamatan Bandungan Kabupaten Semarang - Arif Hidayat; Pujiono Pujiono; Saru Arifin; Laga Sugiarto (Journal of Dedicators Community, 2020)
Jetis Village has SMEs that are engaged in modeste (sewing and embroidery) which are still implemented with conventional systems in terms of production, management and marketing. This makes SME Partners have some security when they have to face the big order season or when they have to compete with other similar SMEs that have developed modern management. UKM players who are mostly the attention in this service. This service method is 1) Observation; 2) Focus Group Discussions; 3) Dissemination; and 4) Evaluation. The results of this service are 1) activities focused on partner networking, managerial strengthening, and online marketing training through social media; 2) SME Partners understand the managerial processes that are recorded and monitored starting from financial managerial, human resources, and production raw materials; 3) SME Partners are facilitated by related agencies to have networks with raw material suppliers and potential market candidates; 4) SME Partners own and are able to assist Facebook Pages which are used for online marketing.